Electrochemical degradation of methylene blue using Ce(Iv) ionic mediator in the presence of Ag(I) ion catalyst for environmental remediation - Setiyanto, Henry; Feni Mustika Sari,; Azis, Muhammad Yudhistira; Ria Sri Rahayu,; Sulaeman, Amminudin; Zulfikar, Muhammad Ali; Diah Ratnaningrum,; Vienna Saraswaty, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Methylene blue (MB) is often used in textile industries and is actively present in the wastewater runs-off. Recently, mediated electrochemical oxidation (MEO) offers a fast, reliable and promising results for environmental remediation. Thus, we aimed to evaluate the electro-degradation potential of MB by MEO using Ce(IV) ionic mediator. Furthermore, we also observed the influence of addition Ag(I) ion catalyst in MEO for degradation of MB. The electro-degradation of MB was evaluated by cyclic voltammetry technique and was confirmed by UV-Vis spectrophotometry, high performance liquid chromatography (HPLC) analysis and back-titration analysis. The results showed that in the absence of Ag(I) ion catalyst, about 89 % of MB was decolorized within 30 min. When 2 mM of Ag(I) ion catalyst was applied, the electro-degradation of MB was increased to maximum value of 100%. The UV-Vis spectrum confirmed the electro-degradation of MB as suggested by decreased maximum absorbance value at λ 668 nm from 2.125 to 0.059. The HPLC analysis showed the formation of five new peaks at retention time of 1.331, 1.495, 1.757, 1.908, and 2.017 min, confirming the electro-degradation of MB. The back-titration analysis showed about 52.9% of CO2 was produced during electro-degradation of MB by MEO. More importantly, more than 97% of Ce(IV) ionic mediator were recovered in our investigation. Our results showed the potential of MEO using Ce(IV) ionic mediator to improve the wastewater runs-off quality from textile as well as other industries containing methylene blue.